1990
DOI: 10.1093/oxfordjournals.aje.a115678
|View full text |Cite
|
Sign up to set email alerts
|

Diet and the Risk of Invasive Cervical Cancer Among White Women in the United States

Abstract: A case-control study of incident invasive cervical cancer was conducted in Birmingham, Alabama; Chicago, Illinois; Denver, Colorado; Miami, Florida; and Philadelphia, Pennsylvania, during 1982-1983. Controls were selected by random-digit dialing and were matched to cases by age, race, and telephone exchange. Of the white, non-Hispanic cases and controls identified, 271 (73%) and 502 (74%), respectively, were successfully interviewed. Diet was assessed by asking about the usual adult frequency of consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 30 publications
0
24
1
2
Order By: Relevance
“…Liu et al (1993) found no association between calcium intake and cervical dysplasia, with a multivariate-adjusted OR for the highest to lowest level of intake of 0.9 (95% CI 0.4-2.1; trend P ¼ 0.58). Ziegler et al (1990Ziegler et al ( , 1991 showed no association between dairy product intake and carcinoma in situ or invasive cervical cancer. Furthermore, to our knowledge, the association between vitamin D and cervical neoplasia has not been analyzed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Liu et al (1993) found no association between calcium intake and cervical dysplasia, with a multivariate-adjusted OR for the highest to lowest level of intake of 0.9 (95% CI 0.4-2.1; trend P ¼ 0.58). Ziegler et al (1990Ziegler et al ( , 1991 showed no association between dairy product intake and carcinoma in situ or invasive cervical cancer. Furthermore, to our knowledge, the association between vitamin D and cervical neoplasia has not been analyzed.…”
Section: Discussionmentioning
confidence: 89%
“…Vitamin D modulates calcium metabolism, inhibits cellular proliferation, induces differentiation and apoptosis and (Ziegler et al, 1991) inhibits angiogenesis in normal and malignant breast cells Xue et al, 1999;Shin et al, 2002;Cui and Rohan, 2006;Deeb et al, 2007). With regard to cervical cancer, however, only a few epidemiological studies have sought to determine the association between calcium and vitamin D and cancer risk (Ziegler et al, 1990(Ziegler et al, , 1991Liu et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ziegler et al (1990Ziegler et al ( , 1992, this dose-response curve relationship can be observed during prenatal glutamine supplementation in humans, particularly following bone marrow transplantation. For some supplements, such as β-glucan, a characteristic dose-response curve is observed at any given time point.…”
Section: Discussionmentioning
confidence: 96%
“…One of the first studies reporting the safety of glutamine use in clinical nutrition was conducted by Ziegler et al (1990). According to their study, the metabolic effectiveness of glutamine in bone marrow transplantation was observed at a dose of 0.57 g glutamine/kg bw/day (Ziegler et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effect of dietary intake of Vitamin A on the risk of cervical cancer or dysplasia, a precursor of cervical cancer, have yielded conflicting results. Some have reported that lower intake levels of dietary retinol or beta-carotene were associated with an elevated risk of cervical cancer or dysplasia (Marshall et al, 1983;Liu et al, 1993;WylieRosett et al, 1984), whereas others did not (De Vet et al, 1991;Ziegler et al, 1990;La Vecchia et al, 1988). Findings from serum investigations have also been inconsistent.…”
mentioning
confidence: 99%